2016
DOI: 10.1111/nep.12702
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐eight‐year review of childhood renal diseases from renal biopsy data: A single centre in China

Abstract: The incidence patterns of paediatric renal diseases changed over the 28-year period of this study. Our results show that different renal diseases characterize different age intervals. Furthermore, there are several associations between clinical presentation and biopsy features in childhood renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 10 publications
5
13
0
Order By: Relevance
“…In our series, there was a predominance of boys (68%), which was consistent with previous studies that reported a higher proportion of boys in patients with pediatric glomerulopathy (6,8,25,28). It might be attributable to the higher susceptibility of boys to major glomerular diseases, such as minimal change disease and IgA nephropathy.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our series, there was a predominance of boys (68%), which was consistent with previous studies that reported a higher proportion of boys in patients with pediatric glomerulopathy (6,8,25,28). It might be attributable to the higher susceptibility of boys to major glomerular diseases, such as minimal change disease and IgA nephropathy.…”
Section: Discussionsupporting
confidence: 92%
“…Mesangial proliferative GN was reported to be the most common glomerulopathy in India (33), whereas IgA nephropathy was reported as the most frequent pattern of pediatric glomerular disease in Korea (34) and Italy (35). In several single-center studies conducted in China (25,36), minimal change disease or IgA nephropathy was identified as the most common pediatric glomerular disease. The variation in the spectrum of pediatric glomerulopathies in studies from different countries may result from the differences in biopsy indications, patient referral, and racial predisposition to different nephropathies (25,37,38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We read with interest the recent publication by Jiang et al reporting the clinicopathological characteristics of biopsy‐proven childhood renal diseases at a centre in Guangzhou, China. Notably, the third leading cause of primary glomerular disease after IgA nephritis (27.6%) and minimal change disease (24.0%) was “mesangial proliferative glomerulonephritis” (16.9%), a diagnosis 2.7 times more frequent than focal segmental glomerulosclerosis (6.3%) and 4.6 times more frequent than endocapillary proliferative glomerulonephritis (3.7%).…”
mentioning
confidence: 99%